*Z podanego wzoru wyznacz niewiadomą : y. Załóż, że wszystkie niewiadome są liczbami dodatnimi.

a). 2y - ab = c
b). b = -ay + dv
c). ay - c = 4ay - d

* Z podanego wzoru wyznacz niewiadomą : z . Załóż , że wszystkie niewiadome są liczbami dodatnimi.

a). z/a = b/z

3

Odpowiedzi

2010-04-11T19:26:05+02:00
1
a). 2y - ab = c
2y=c+ab
y=(c+ab)/2

b). b = -ay + dv
-ay=b-dv
y=(b-dv)/-a
y=(dv-b)/a

c). ay - c = 4ay - d
ay-4ay=-d-c
y(a-4a)=-d-c
y=(-d-c)/-3a
y=(d+c)/3a

2..
a). z/a = b/z |*z *a
z²=ba
z=√ba
2 5 2
2010-04-11T19:28:38+02:00
2y - ab = c / +ab
2y=c +ab /:2
y=c+ab/2

b = -ay + dv / *(-1)
-b=ay-dv /+dv
-b+dv=ay /:a
y= -b+dv/a


ay - c = 4ay - d
ay-4ay=-d+c
-3ay=c-d /: (-1)
3ay=-c+d /:3a
y=-c+d/3a
2 5 2
2010-04-11T19:29:32+02:00
A) 2Y - AB=C
2Y=C+AB/:2
Y=C+AB/2

b) b=-ay+dv
ay=dv-b/:a
y=dv-b/a

c)ay-c=4ay-d
ay-4ay=c-d
-3ay=c-d/: (-3a)
y=c-d/-3a


3 5 3